The regulation of nitric oxide in tumor progression and therapy. Issue 2 (February 2020) - Hu, Ya; Xiang, Jing; Su, Linlin; Tang, Xi
Nitric oxide (NO) is a ubiquitous gas with free radical groups that is soluble in water, and which is involved in numerous physiological functions including inflammatory and immune responses. However, the role of NO in tumor biology is controversial and misunderstood. NO has been shown to have both anti-cancer and carcinogenic effects, which are dependent on the time, location, and concentration of NO. This duality presents a double challenge to determine the net impact of NO on cancer and to define the therapeutic role of NO-centered anti-cancer strategies. Nevertheless, it is believed that a comprehensive and dynamic understanding of the cascade of molecular and cellular events underlying tumor biology that are affected by NO will allow researchers to exploit the potential anti-tumor properties of drugs that interfere with NO metabolism.